Impact of Social Media on English Language Evolution (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2025)
The evolution of the English language has been significantly influenced by various factors over time, with social media emerging as a powerful force in recent decades. This research paper explores the impact of social media on the development of the English language, focusing on the ways in which it has affected vocabulary, grammar, and communication styles.